Assessing proposals for a transatlantic free trade area - Rolf J. Langhammer; Daniel Piazolo; Horst Siebert (Aussenwirtschaft, 2002)
Initiatives to reduce transatlantic trade barriers or to harmonize trade-related domestic policies in the EU and the US appear regularly on the agenda of policy makers. The last decade saw also considerable steps in transatlantic economic cooperation focusing on special aspects. In February 2002, a new call for a study on the benefits of a transatlantic free trade area (TAFTA) was made by the President of the EU Council to facilitate further liberalization schemes. This article examines recent developments in transatlantic economic policies, discusses changes in approaches in transatlantic regionalism and presents estimates of the economic consequences of transatlantic liberalization. Given the expected small benefits of a TAFTA and the induced costs for multilateral liberalization negotiations, the article discusses alternatives to TAFTA and argues for a multilateral approach, eventually being accompanied by some sort of open regionalism.
Keywords: 330; Außenhandelsliberalisierung; Freihandelszone; EU-Staaten; USA